Organizational Citizenship Behavior (OCB): How Leadership and Competency Inspire Performance - Anggoro KR, M. Yusuf Alfian Rendra (PT FORMOSA CENDEKIA GLOBAL, 2024)
Its goal is to assess the impact of Leadership and Competency on Performance through Organizational Citizenship Behavior (OCB)hraser!. This research is a case study of the Boalemo Regency Regional Government. The population in this study were all employees from the entire Boalemo Regency Regional Government with a total population of 1,569. Then it was simplified using the Slovin formula so that the sample was 236 and analyzed using Structural Equation Modeling (SEM). The research results show that: 1) Leadership has a positive and significant effect on Organizational Citizenship Behavior (OCB), 2) Competence has a positive but not significant effect on Organizational Citizenship Behavior (OCB), 3) Leadership has a positive and significant effect on performance, 4) Competency has a negative and insignificant effect on performance. 5) Organizational Citizenship Behavior (OCB) has a positive and significant effect on Performance, 6) Leadership through Organizational Citizenship Behavior (OCB) has a positive and significant effect on Performance, 7) Competence through Organizational Citizenship Behavior (OCB) has a negative and insignificant effect on performance.